Does Decreased SNX10 Serve as a Novel Risk Factor in Atrial Fibrillation of the Valvular Heart Disease? - A Case-Control Study - Yao, Jianping (Braz J Cardiovasc Surg, 2021)
INTRODUCTION: Atrial fibrillation (AF) is the most common sustained arrhythmia. Sorting nexin 10 (SNX10) has been reported to be an important regulator in embryonic development and human diseases, however, little is known about its role in cardiac disease. The aim of this study was to investigate the clinical significance of SNX10 expression in AF. METHODS: Nineteen valvular heart disease patients with AF and nine valvular heart disease patients with sinus rhythm (SR) were enrolled. Atrial tissue samples from patients undergoing open heart surgery were examined. Atrial tissues of normal hearts were obtained from two cases’ autopsies. The SNX10 expression and its associations with the degree of fibrosis were analyzed by immunohistochemistry and Masson’s trichrome staining. RESULTS: SNX10 expression was detected in the cytoplasm of cardiac cells in human myocardial tissue. The SNX10 expression level was higher in the SR group than in the AF group (P=0.023). SNX10 expression was negatively associated with the degree of fibrosis (P=0.017, Spearman rho=-0.447), the New York Heart Association degree (P=0.003, Spearman rho=-0.545), left atrial diameter (P=0.038, Spearman rho=-0.393), right atrial diameter (P=0.043, Spearman rho=-0.386), and the brain natriuretic peptide (BNP) level 24 hours after surgery (P=0.030, Spearman rho=-0.426), but not the BNP level before surgery and 72 hours after surgery. No statistical significance was observed between SNX10 and the level of troponin T and C-reactive protein. CONCLUSION: Decreased SNX10 might serve as a potential risk factor in AF of the valvular heart disease.